Back Cover Image, Volume 5, Number 4, April 2023. Issue 4 (25th April 2023) - Song, Yingze; Zou, Luwei; Wei, Chaohui; Zhou, Yu; Hu, Yue
Abstract : Back cover image : Featuring isolated dispersed metal atoms on a substrate, single atom catalysts (SACs) have emerged as a new frontier in lithium‐sulfur battery (LSB) realm thus far. In the tutorial review (number: 10.1002/cey2.286 ), Song et al . systematically summarized the design principle, typical fabrication of SACs and their latest advancements in manipulating the sulfur and lithium evolutions. Further, the intractable challenges and possible opportunities for SACs are also proposed, aiming at helping to break through the gap between academic investigations and real implementation of LSBs.